A comprehensive review of experimental approaches used in the measurement of springback - Abdullah, Ahmad Baharuddin; Salit, Mohd Sapuan; Samad, Zahurin; Abdul Aziz, Nuraini (American-Eurasian Network for Scientific Information, 2012)
Springback is one of a significant problem in the sheet metal forming. There are a number of effort taken in predicting and quantifying the springback experimentally. In this research, few design and process parameters that affect the performance of the formed sheet had been outlined. This paper will review the springback measurement approaches via experimental method. The discussion involves with the theoretical background of the springback, recent approaches and most of the studies conducted and reported. Most of the studies and parameters taken into consideration in the experimental will be discussed in details. The recent issues and problems within the current approaches will be highlighted. The paper also raised the issue of twist forming process, where the amount of springback found to be larger, and this process is much more complex process compared to other bending processes.